Bioinspired First Stereoselective Total Synthesis of Spinosulfate B. Issue 31 (16th August 2019) - Bokam, Ramesh; Annam, S. CH. V. Appa Rao; Yalavarthi, Nageswara Rao; Gundoju, Narayanarao; Ponnapalli, Mangala Gowri
Abstract: An efficient bioinspired stereoselective first total synthesis of spinosulfate B has been accomplished following Jacobsen's hydrolytic kinetic resolution, Stille coupling, olefin‐cross metathesis (OCM), Horner Wadsworth Emmons olefination, and De Brabander's esterification as key steps. Abstract : An efficient bioinspired stereoselective first total synthesis of Spinosulfate B has been achieved following Jacobsen's hydrolytic kinetic resolution, Stille coupling, olefin‐cross metathesis (OCM), Wittig Horner olefination, and De Brabander's esterification as key steps. This synthetic strategy should find wide application in the synthesis of structurally related bioactive dimeric alkylresorcinols (ARs) and also the facile reaction protocol opens up the scope of the current synthesis in larger quantities for screening purposes and biological studies.